Obraz Wojska Polskiego i podziemia poakowskiego w latach 1945-1946 w świetle raportów czechosłowackiego wywiadu = Picture of the Polish Army and anti-communist resistance in Poland in years 1945-1946 in light of the Czechoslovak intelligence reports - Halczak, Bohdan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In years 1945-1946 the Czechoslovak intelligence had operated Poland. Secret intelligence reports are now a valuable resource for historians. In years 1945-1946, in the mountainous regions of southeastern Poland, near the border with Czechoslovakia lasted civil war. Government forces and anticommunist resistance fought with each other. Events in south-eastern Poland were carefully observed by Czechoslovak intelligence. Czechoslovak agents critically evaluated government forces.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia